Analisis Tingkat Pencahayaan Ruang Kelas Gedung Fakultas Teknik Universitas Krisnadwipayana Menggunakan Dialux - Bayu Kusumo; Wisnu Dwi Antoro (Teknik Elektro Universtias Krisnadwipayana, 2024)
Lighting in a building, especially in the lecture building, is very necessary for lighting with good quality. This study aims to determine the quality of lighting in the lecture room of Building G, Faculty of Engineering, Krisnadwipayana University using the dialux application to simulate it. The relationship between space and light, space will always surround human existence, in space, visual form, quality of light, dimensions and scale are determined by the boundaries that have been determined by the elements of form. This study performs calculations using the lamp equation, measurements using a luxmeter and visualization using Dialux evo 9.2. The results of the calculation with the equation of the lamps installed are the lighting quality of class room 203 which is only 57.52 lm, class room 204 is 68.81 lm and study program office space which is only around 68.81 lm. With the results of measurements of room 203 with an average of 45.43 lux for local measurements and general lighting of 54.25 lux, for room 204 local measurements were at 48.93 lux and general lighting measurements were 63.37 lux, for the room of the Head of Study Program the local measurements were 54.25 for general exposure measurements. In the dialux analysis, the lighting levels for Room 203, Room 204, and Room for Head of Study Programs are 39.9 lux, 45.1 lux, 41.9, respectively. From all the data obtained from the analysis of the three sample rooms that represent all the rooms have not reached the Indonesian national standard. To be able to achieve lighting results in accordance with the standard, it is necessary to increase the number of lamps or replace lamps with higher luminance value